2023
DOI: 10.1021/acsami.2c20482
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effect of α-ZrP Nanosheets and Nitrogen-Based Flame Retardants on Thermoplastic Polyurethane

Abstract: A supramolecular self-assembly method was used to prepare melamine cyanurate/α-ZrP nanosheets (MCA@α-ZrP) as a novel hybrid flame retardant for thermoplastic polyurethane (TPU). Microstructure characterization showed a uniform dispersion with strong interfacial strength of the MCA@α-ZrP hybrid within the TPU matrix, leading to simultaneous enhancements in both mechanical and fire-safety properties. The TPU/MCA@α-ZrP nanocomposite exhibited 43.1 and 47.0% increments in tensile strength and fracture energy, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…The well-ordered lamellar structure usually improves the carbonization degree of char residues; this forms impermeable char layer which can stop/slow down the flow of volatile gases and mass heat to fortify the flames. 19 The flame-retarding mechanism will be elucidated in the following sections.…”
Section: Thermal Stabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…The well-ordered lamellar structure usually improves the carbonization degree of char residues; this forms impermeable char layer which can stop/slow down the flow of volatile gases and mass heat to fortify the flames. 19 The flame-retarding mechanism will be elucidated in the following sections.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…It is noteworthy to mention that the tensile strength of the ABS/La@PN-RGO composite increased by 16% without compromising its strain at break. Zirconium phosphate (α-ZrP) nanosheets were also studied as reinforcing filler and a FR additive; 19 α-ZrP nanosheets have high thermal stability and ion-exchange feature and are able to intercalate and/or exfoliate within the host matrix. Recent research showed that α-ZrP can act as an active solid acid catalyst to improve the flame retardancy of polymers due to its Lewis acid sites on its surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the effect of the polymer matrix of peelable coatings on the tunable adhesion and cohesion, the performance (i.e., type, content, or structure) of the microwave absorber also affects the trade-off in adhesion and cohesion . The presence of microwave absorber can increase the cohesive strength and stiffness of coatings, which are associated with the control of adhesion. , The filler contents will inevitably affect the structural integrality and energy dissipation under the external force of the coating, which is vital for the desirable peelability. Therefore, in view of the complex and diverse chemical/physical bonds and surface-interface interactions between the microwave absorber and polymer matrix of coating, developing a simple and novel peelable MA coating system is highly desired.…”
Section: Introductionmentioning
confidence: 99%